JENIS ALGA MERAH (RHODOPHYTA) PADA EKOSISTEM HUTAN MANGROVE DI DUSUN EKAS, KABUPATEN LOMBOK TIMUR - Mursal Ghazali; Rika Rahmawati; Sri Puji Astuti; Sukiman Sukiman (Fish Scientiae, 2018)
Mangrove ecosystem is a unique ecosystem with a mix of marine and terrestrial environment. Mangrove forests provide food and nutrients for other organisms such as fish,crustaceans, and algae. Red algae play an important role in maintaining the balance of ecosystems and food chains. This study aims to determine the types, morphological characteristics and key identification, the relationship of red algae types and substrate types to the ecosystem of mangrove forest in Dusun Ekas. This research is explorative descriptive by using purposive sampling method at 5 stations. Based on the results of the red algae study obtained as many as 14 species are: Bostrychia sp., B. radicans, B. tenella, Chondria sp., Laurencia sp., Polysiphonia sp., Murrayella sp., C. Leprieurii, C. Monostica, Gelidium sp ., Gelidium crinale, Catenella caespitosa, Catenella nippae and Catenella sp.Characteristics of the talus were found to have a cylindrical talus and some like leaves (blade). Red algae (Rhodophyta) found more in the station that dominated by Soneratia alba species.